JASLAR TÁRBIYASÍNDA MÁHÁLLENIŃ ORNÍ - Djamilova, G. (SCIENCE and SOCIETY, 2025)
This article is dedicated to examining the role of the “mahalla” institution in youth education and its significance in social and spiritual life. The study analyzes the activities of the “mahalla” in shaping moral values among youth, increasing social activity, and instilling respect for national culture. Based on quantitative method, the strengths and weaknesses of the mahalla's activities were identified, and recommendations for improving the educational process were developed. This article holds both practical and scientific significance for strengthening the role of the mahalla in youth education.